Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.compstruct.2016.12.041
|View full text |Cite
|
Sign up to set email alerts
|

On Extension-Shearing Bending-Twisting coupled laminates

Abstract: This article presents details of the development of a special class of laminate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…Recent research has led to laminate design databases containing Extension-Shearing [1] and/or Bending-Twisting coupling [2]. The results have demonstrated that the design spaces contain predominantly non-symmetric stacking sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has led to laminate design databases containing Extension-Shearing [1] and/or Bending-Twisting coupling [2]. The results have demonstrated that the design spaces contain predominantly non-symmetric stacking sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The theory behind the algorithm used to generate the designs presented here is given elsewhere [9,10,11,12] for each of the 4 laminate classes. Only a summary is therefore provided here, together with details on how the previous derivation for UD laminates has been modified for the purposes of laminates with new NCF architectures.…”
Section: Derivation Of Stacking Sequence Datamentioning
confidence: 99%
“…Extension-Shearing and Bending-Twisting coupled laminates satisfy the following nondimensional parameter criteria [12]:…”
Section: Derivation Of Non-dimensional Parametersmentioning
confidence: 99%
See 2 more Smart Citations